Building the Green Entrepreneur Spirit of Students: The Influence of Entrepreneurship Course and Entrepreneurial Motivation through Entrepreneurial Attitude - Alim Bahri; Ilma Wulansari Hasdiansa (Pinisi Journal of Entrepreneurship Review, 2024)
Entrepreneurship is something that is identified with what entrepreneurs or entrepreneurs have and do. This view is inaccurate because the entrepreneurial spirit and attitude are not only possessed by entrepreneurs, but also by everyone who thinks creatively and acts innovatively, for example farmers, employees, students, and teachers. Entrepreneurs are those who make creative and innovative efforts by developing ideas and gathering resources to find opportunities and improve life. The aim of this research is to explain the influence of entrepreneurship education on the motivation of Entrepreneurship students at the Faculty of Economics and Business, Makassar State University, considering that entrepreneurship education is not evenly distributed among students, or in other words, not all study programs in universities provide entrepreneurship courses. This research approach is a quantitative approach with a correlational research design. Population the research consisted of all 102 UNM Entrepreneurship Students. Meanwhile, the sampling technique uses the Proportional Random Sampling technique, which is calculated using Slovin with a sample of 100 respondents or 22% of the total population. The research method used in this research is quantitative. This research can be a source of information or reference for teaching staff or lecturers so that they can direct and guide students regarding developing entrepreneurial interests. Students are also expected to deepen their interests related to business management so that they are not only focused on the knowledge they produce but are also able to do business. business and develop it.